Mass spectrometry-based identification of 26 Pasteurella species and in vitro antimicrobial susceptibility pattern of isolates recovered from diseased domestic cats - Carolina A. Rodrigues; Marcelo F. Arabe Filho; Thais S. Bello; Fábio V.R. Portilho; Fernando J.P. Listoni; Fábio S. Possebon; Patrik Jr. L. Paz; Paulo C.L. Eliam; Márcio G. Ribeiro (Pesquisa Veterinária Brasileira)
ABSTRACT: Pasteurella species are well-known opportunistic bacteria that inhabit the microbiota of the oral cavity and upper respiratory tract of cats and have been related to a set of pet-associated diseases in addition to humans. Most studies involving feline pasteurellosis have been described as case reports and species identification based on classic phenotypic methods. In turn, a lack of comprehensive studies involving a great number of cats with pasteurellosis has been described, especially where diagnosis at the species level has been performed by molecular-based methods. In this scenario, we investigated the molecular identification of Pasteurella species isolated from 26 diseased domestic cats (i.e., cutaneous abscesses, pneumonia, conjunctivitis, open wounds, urinary tract infections, pleural effusion, pyometra, and infection secondary to neoplasia) based on proteomic diagnosis, using mass spectrometry (matrix-assisted laser desorption ionization time-of-flight mass spectrometry - MALDI-TOF MS). The in vitro antimicrobial susceptibility patterns of isolates and selected epidemiological data (with emphasis on the outcome) were assessed as well. MALDI-TOF MS identified predominantly P. multocida (23/26=88.5%), followed by P. dagmatis (2/26=7.7%) and P. canis (1/26=3.8%). The isolates revealed 100% susceptibility to beta-lactams (amoxicillin/clavulanic acid, ampicillin, cephalexin, ceftriaxone), tetracyclines (tetracycline, doxycycline) and fluoroquinolones (ciprofloxacin, levofloxacin, marbofloxacin) groups of antimicrobials. Conversely, the highest resistance of the isolates was observed for amikacin (10/26=38%). Data on outcomes were available for 61% (16/26) of cats, of which 50% (8/16) died or were subjected to euthanasia due to severe complications (e.g., sepsis, pneumonia, and pleural effusion) secondary to disseminated/systemic infections, although no significant association was observed between Pasteurella species and the clinical-epidemiological findings studied. Our results contribute to the molecular identification of Pasteurella species and vigilance of multidrug-resistant bacteria that infect cats. Also, it highlights the need for the early diagnosis and therapy of feline pasteurellosis due to high mortality rates.